Systematic Literature Review (SLR): The Influence of Digital Literacy and Entrepreneurship Education on Interest in Digital Entrepreneurship - Ali, Himatul Fitria; Kamalia, Putri Ulfa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Low interest in digital entrepreneurship has become a serious problem amidst increasing competition in the workplace and an imbalance between workforce growth and job availability. This condition contributes to rising unemployment, especially among the younger generation. This study aims to examine the influence of digital literacy and entrepreneurship education on interest in digital entrepreneurship using a Systematic Literature Review (SLR) approach. The selection of digital literacy variables is based on the importance of an individual's ability to access, understand, and utilize digital technology as a foundation for running a digital-based business. Meanwhile, entrepreneurship education was chosen because of its crucial role in shaping entrepreneurial attitudes, knowledge, and skills that encourage individuals to start and develop businesses. Through a systematic review of various previous studies, this study is expected to provide a comprehensive overview of the strategic role of these two variables in increasing interest in digital entrepreneurship in the current era of digital transformation.